Patients' evaluations of European general practice: revisited after 11 years - Petek, Davorina; Künzi, Beat; Kersnik, Janko; Szecsenyi, Joachim; Wensing, Michel (International journal for quality in health care, 2011)
BACKGROUND: In the last decade many things have changed in healthcare systems, primary care practices and populations. - OBJECTIVE: To describe evaluations of general practice care by patients with a chronic illness in 2009 and compare these with a previous study done in 1998. - DESIGN: A descriptive analysis of patients' evaluations, using data from the European practice assessment Cardio study on cardiovascular patients in eight European countries in 2009. We compared these evaluations with a subgroup of patients with self-defined chronic illness from the study in 1998, using a linear regression model. - MAIN OUTCOME MEASURE: Patients' evaluation of general practice using the EUROPEP questionnaire. The EUROPEP is a 23-item validated measure of patient evaluations of general practice care. - RESULTS: In 2009, 7472 patients from 251 practices participated in the study with an overall response rate of 49.6%. The percentage of patients with positive evaluations (good/excellent) was 80% or higher for all items, except for the waiting time. More positive evaluations were found in older patients, patients with a longer attachment to the practice, patients with a higher self-evaluation of their health, patients with fewer mental health problems and less pain/discomfort. The comparison between 1998 and 2009 showed no overall trends for all countries combined. Whereas English patients became fairly more positive about general practice in 2009, German patients became slightly less positive, although still more positive than English patients. - CONCLUSION: Overall, the patients' evaluations of general practice were very positive in family practice care in the years 1998 and 2009. The trends over the years need to be carefully interpreted over time.